Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/bem.22262
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Frequency Magnetic Field of Appropriate Strengths Changed Secondary Metabolite Production and Na+ Concentration of Intracellular and Extracellular Monascus purpureus

Abstract: Monascus purpureus is used to yield edible pigments accompanied by mycotoxin-citrinin. A low-frequency (<300 Hz) magnetic field (LF-MF) affects microbial metabolism. The link of LF-MF with secondary metabolites and intracellular and extracellular Na + levels in M. purpureus was determined. The fermentation broth was exposed to LF-MF during the first 2 days of fermentation and continuously cultured at 30°C and 200 rpm until the 8th day of fermentation. Results showed that LF-MF treatments didn't affect the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…36 LF-MF promoted the biosynthesis of MPs. [40][41][42][43] This study also found that 250 lux red light treatment M. purpureus 24 h significantly promoted the production of water-and alcohol-soluble MPs in WT. The the yield of MPs had a significant increase in WT exposed to RLCMF.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…36 LF-MF promoted the biosynthesis of MPs. [40][41][42][43] This study also found that 250 lux red light treatment M. purpureus 24 h significantly promoted the production of water-and alcohol-soluble MPs in WT. The the yield of MPs had a significant increase in WT exposed to RLCMF.…”
Section: Discussionsupporting
confidence: 63%
“…For M. purpureus, it affected the growth and MPs production. [40][41][42][43] Light and MF, as natural environmental factors, affected the growth, development, and MPs biosynthesis of Monascus. Histone H3K4 methylation was often accompanied by the activation of gene transcription, which also affected the MPs biosynthesis of Monascus.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the regulation of gene expression in mycotoxin biosynthesis helps to explain and develop control approaches by linking the environmental factors inducing toxin synthesis. For example, a treatment by a low-frequency (<300 Hz) magnetic field inhibits CIT contamination by reducing the expression of the pathway-specific regulator gene ctnA in M. purpureus [ 139 ]. Another potential strategy is to identify molecules that could inhibit pathway-specific regulators.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…40 In line with the results, Xiong et al further confirmed that under 1.6 mT treatment, the yellow and red pigment yield of M. purpureus was promoted by over 70%, accompanied by decreased citrinin content. 41 Two possible underlying mechanisms were concluded as follows: one is that the low-frequency (<300 Hz) magnetic field (LF-MF) can up-regulate transcriptional levels of some key pigment production genes and significantly suppress the transcriptional levels of citrinin genes. The other is that the LF-MF can alter polyketide metabolic flux from citrinin to pigment synthesis.…”
Section: Optimization Of Culture Conditionsmentioning
confidence: 99%